PENILAIAN KINERJA DENGAN MENGGUNAKAN KONSEP 360 DERAJAT FEEDBACK - Widya, Rita (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2004)
Abstract The concept of 360 degree appraisal is straight forward enough. In the systems, individuals evalute themselves and receive feedback from other employees and organizational members. The feedback comes from an individuals immediate supervisor and peers, and if the individual is manager from his or her direct subordinates. Employees performance can improved through feedback with evaluate themselves and receives feedback from other employees. With apply the concept of 360 degree feedback for getting effective performance appraisal result. Â  Keywords: Performance appraisal, the concept of 360 degree feedback